Itinerário terapêutico percorrido por familiares de crianças com transtorno do espectro autista - TEA - LIMA, Nádia Alexandrina Coutinho (2023)
Autism spectrum disorder (ASD) is a developmental disorder that can be recognized by deficits in social communication and social interaction; expressive deficits in verbal and non-verbal communication; restricted and repetitive patterns of behavior, interests and activity. Despite the existence of public policies aimed at the care of people with autism, the trajectory of these people and their families does not seem to coincide with the flowcharts proposed by the national guidelines for care for this population. In view of the above, this research aims to understand the path taken by parents or guardians of children with autism spectrum disorder in the health network in the city of Crateús-CE, from the identification of the first signs to the diagnosis and access to therapeutic interventions, from the perspective of their family members. The aim is to characterize the actors involved with sociodemographic indicators, identify the support network variables attributed by parents or guardians of children with ASD and identify the support network care points mentioned by parents or guardians of children with ASD. Method: This is a descriptive study, with a qualitative approach, using the cartographic method and the use of an Affective Map generating instrument to collect data, through focus groups, using a semi- structured interview. Eight family members of children with autism spectrum disorder - ASD in the municipality of Crateús – Ce, who are part of the Association of Mothers of Autistics of Crateús - AMAC, participated in the research. The interviews and groups were analyzed using discourse analysis, organized into categories and subcategories. Results: The therapeutic itinerary is characterized by the identification of the first signs and therapeutic intervention before the diagnosis, the search for the diagnosis that was seen to face many barriers, including access to rehabilitation services and the diagnosis that comes loaded with feelings and demands of family changes. Final considerations: The study revealed that despite the existence of public policies aimed at caring for people with ASD and their families, there is still a gap between the guidelines for health practices and the actual practices. There is fragility in access to health services, leading families to seek support from health plans and little pressure and activism for their rights.